THE EFFECTIVE HUMAN RIGHTS IN MULTICULTURAL DESIGN: CONSTRUCTION OF CITIZENSHIP COSMOPOLITAN - Muller, Crisna Maria (2016)
This article investigates the imposition of Western hegemonic discourse of human rights globally in favor of economic and liberal interest. Furthermore, we intend to deepen the construction of a counter-hegemonic discourse of human rights, multicultural contribution and outlines the elements of cosmopolitan citizenship, which develop within encounter between different cultures and change agents. To achieve the proposed objectives, the study applied the inductive method and the search procedure documentary and literature. The findings indicate that the liberal hegemonic discourse of human rights exposes its limitations presenting himself as the be global human emancipation path. Thus, only by a kind of counter-hegemonic hermeneutics is that human rights can be effective as cosmopolitan politics